Identification of Physical Interaction in Binary Systems of Acyclovir – Succinic Acid - Agnes Nuniek Winanta; Dwi Setyawan; Siswandono Siswandono (Universitas Airlangga, 2016)
Background: Acyclovir, a guanosine analogue antiviral drug with low solubility of water. Due to its poor solubility and permeability, causes low oral bioavailability. Objective: The aim of this research is to investigate the physical interaction in binary systems acyclovir-succinic acid (AS). Methods: The msystem was prepared by solvent evaporation method. Results: Thermogram Differential Scanning Calorimetry showed endothermic peaks at 172.68oC (ethanol) and 171.84oC (methanol). The Powder X-Ray Diffraction (PXRD) pattern of AS was different from pure component and physical mixtures. Furthermore, physical characterization showed the binary system of AS have unique crystal habit by polarization microscope. Conclusion: New crystalline phase is formed from the interaction between acyclovir and succinic acid by solvent evaporation method using ethanol and methanol.